2013
DOI: 10.1038/cddis.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y receptors activation protects rat retinal neural cells against necrotic and apoptotic cell death induced by glutamate

Abstract: It has been claimed that glutamate excitotoxicity might have a role in the pathogenesis of several retinal degenerative diseases, including glaucoma and diabetic retinopathy. Neuropeptide Y (NPY) has neuroprotective properties against excitotoxicity in the hippocampus, through the activation of Y1, Y2 and/or Y5 receptors. The principal objective of this study is to investigate the potential protective role of NPY against glutamate-induced toxicity in rat retinal cells (in vitro and in an animal model), unravel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 58 publications
(98 reference statements)
2
63
4
Order By: Relevance
“…More recently, we showed that microglial cells present NPY Y 1 , Y 2 and Y 5 receptors-IR (Ambrosio et al, 2013;Santos-Carvalho et al, 2013a). Additionally, when these rat retinal cell cultures are exposed to an excitotoxic insult (glutamate), there is an increase of microglia proliferation and activation (Santos-Carvalho et al, 2013b). We also showed that the activation of NPY Y 1 receptor has an anti-inflammatory effect in retinal microglia (Ambrosio et al, 2013), suggesting that NPY system can be targeted as a strategy to delay the progression of retinal degenerative diseases with a neuroinflammatory component.…”
Section: Microglial Cells Microglial Cells Are Involved In Neuronal mentioning
confidence: 95%
See 2 more Smart Citations
“…More recently, we showed that microglial cells present NPY Y 1 , Y 2 and Y 5 receptors-IR (Ambrosio et al, 2013;Santos-Carvalho et al, 2013a). Additionally, when these rat retinal cell cultures are exposed to an excitotoxic insult (glutamate), there is an increase of microglia proliferation and activation (Santos-Carvalho et al, 2013b). We also showed that the activation of NPY Y 1 receptor has an anti-inflammatory effect in retinal microglia (Ambrosio et al, 2013), suggesting that NPY system can be targeted as a strategy to delay the progression of retinal degenerative diseases with a neuroinflammatory component.…”
Section: Microglial Cells Microglial Cells Are Involved In Neuronal mentioning
confidence: 95%
“…The neuroprotective effects of NPY against excitotoxicity have been investigated in different CNS regions, and also in the retina (Alvaro et al, 2008b(Alvaro et al, , 2009Santos-Carvalho et al, 2013b;Silva et al, 2003Silva et al, , 2005Smialowska et al, 2009;Xapelli et al, 2006Xapelli et al, , 2007. We have shown that NPY protects retinal neurons against 3,4-methylenedioxymethamphetamine (MDMA)-induced toxicity in rat retinal neural cell cultures (Alvaro et al, 2008b).…”
Section: In Contrast Npy Stimulates the Release Of [ 3 H]-glycinementioning
confidence: 99%
See 1 more Smart Citation
“…Y2 and Y4 receptors are involved in the protective effect of neuropeptide Y against necrotic, while Y5 against necrotic and apoptotic cell death induced by glutamate (Santos-Carvalho et al, 2013).…”
Section: Neuroprotectantsmentioning
confidence: 99%
“…In order to assess the potential neuroprotective effects mediated by A 3 R activation, TUNEL assay ( Figure 1A and B) was performed in a primary retinal neural cell culture, well characterized in our lab (Costa et al, 2009;Santiago et al, 2007;Santos-Carvalho et al, 2013b). Retinal cultures were incubated with the selective A 3 R agonist ( …”
Section: Activation Of a 3 Receptor Protects Retinal Cells From Excitmentioning
confidence: 99%